TEACHERS' STRATEGIES IN ASSESSING WRITING IN AN EYL CONTEXT - Widya, Rani Nurcita (2012)
This thesis reported the study on the strategies applied by six English teachers in assessing writing, why the teachers chose those assessment strategies, and to what extent the assessment was appropriate for the teaching programs in an EYL context. This study used a qualitative case study research design which employed three data collection techniques, i.e. class observations, interviews, and document analysis. This study involved six teachers from six elementary schools. The data were analyzed by data reduction, data display, and drawing conclusion. This study revealed, first, the teachers used three strategies of assessing writing. There were portfolio, observation, and K-W-L strategies. The second was the reasons for choosing those strategies. For portfolio strategy, teachers' reasons were that this strategy was easy to be used, teachers could give comments on their works, it was suitable for students in elementary schools, and teachers specifically knew students' mistakes. For observation strategy, their reasons were that teachers could assess students without disturbing students' activities, teachers just prepared the point for assessing, students could not cheat on exam, and the assessment could be used during teaching learning activities. The last was K-W-L strategy. It was what they know, what they want, and what they have learnt. The reasons were that this strategy could be used at the end of the class to know what students have learnt, it was easy for teacher to use this strategy, and teacher just gave directions. The last was that the appropriate assessment for the teaching program was to make the assessment suitable with the syllabus, lesson plan, and the activity in the class. The portfolio and observation strategies were appropriate for teaching program in elementary school. It was proved by the data from class observation, document analysis, and interview. In K-W-L strategy, there was not appropriate material between activity in the class and the lesson plan. Based on these findings, it was concluded that participants had principles in assessing writing to their students. There are suitability, practicality, and comprehensive.